Complete course in astrobiology - Horneck, Gerda; Rettberg, Petra (Weinheim, Wiley-VCH, 2007)
This up-to-date resource is based on lectures developed by experts in the relevant fields and carefully edited by the leading astrobiologists within the European community. Aimed at graduate students in physics, astronomy and biology and their lecturers, the text begins with a general introduction to astrobiology, followed by sections on basic prebiotic chemistry, extremophiles, and habitability in our solar system and beyond. A discussion of astrodynamics leads to a look at experimental facilities and instrumentation for space experiments and, ultimately, astrobiology missions, backed in each case by the latest research results from this fascinating field. Includes a CD-ROM with additional course material.
Index 399-412p.
Keywords: Astrobiology; Physics